Immune Cell Response during COVID-19 Infection and following SARS-CoV-2 Vaccination in Patients Admitted to Intensive Care Unit - Khadija Bahrini; Nejla Stambouli; Mouna Ben Azaiez; Aicha Rebai; Ferid Abid; Chihebeddine Romdhani; Iheb Labben; Hédi Gharsallah; Mustapha Ferjani (Journal of Immunology Research)
Background. Immune response plays a crucial role in virus clearance during COVID-19 infection and underpins vaccine efficacy. Herein, we aimed to assess the immune response during COVID-19 infection and following SARS-CoV-2 vaccination. Methods. In this retrospective study, 94 confirmed COVID-19 patients admitted to the intensive care unit were categorized into unvaccinated patients (n = 50), including 33 deceased and 17 discharged patients, and vaccinated group (n = 44) with 26 deceased and 18 discharged patients. Records of patients with severe COVID-19 admitted to the ICU between March, 2021 and March, 2022 were gathered and analyzed. Result. The assessment of immune cell counts revealed a large rise of neutrophils associated to decrease number of lymphocytes in patients with COVID-19 infection. In dead patients, we detected a significant correlation between neutrophils and inflammatory parameters such as IL-6 and CRP. Moreover, analysis of immune cell count following vaccination did not reveal any significant difference. However, the most substantial result, herein, detected is the decrease level of IL-6 in vaccinated patients as compared to unvaccinated. The reduce level of IL-6 following vaccination is observed in discharged patients as compared to deceased. Regarding the level of mortality after vaccination, we showed that all patients who received the first dose were died (46.1%, n = 12) as compared to those who have received two doses (34.6%, n = 9) and the third dose of vaccine (19.23%, n = 3) (p=0.0018). Strikingly, studying the inflammatory parameters after each vaccine dose, we revealed a significant decrease of IL-6 level after the booster dose (third dose), especially in vaccinated discharged patients. Conclusions. Neutrophils combined with IL-6 and CRP can be very useful markers to predict disease severity in patients admitted to ICU. The decrease level of IL-6 in vaccinated group pointed out the impact of vaccination to prevent inflammatory cytokine release.